Bagaimana Strategi Pemasaran Dengan Mengunakan Artificial Inteligen: Suatu Tinjauan Tematik Dan Eksplorasi Praktis (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to synthesize and describe a comprehensive view of the use of Artificial Intelligence (AI) in marketing strategies. This study is a descriptive exploratory study with thematic review techniques and practical exploration. This study uses the Systematic Literature Review (SLR) method which tries to summarize the use of AI in the stages of marketing strategies. Artificial intelligence is something very phenomenal in the current era of industry 5.0 digitalization. Marketing strategies must be able to adapt to the latest technological developments and also changes in consumer behavior in order to continue to exist in this increasingly tight business competition. Marketing strategies in the era of industry 5.0 based on technology and humanity are a guideline in managing the company's marketing strategy. Artificial intelligence is very important in helping marketers set targets and achieve their goals more effectively and efficiently. From the results of this study, it can be concluded that Artificial Intelligence can be used in implementing every stage of marketing strategy.